2005
DOI: 10.1074/jbc.m501102200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Substrate Specificities of Bacterial Heparinases against N-Unsubstituted Glucosamine Residues in Heparan Sulfate

Abstract: The rare N-unsubstituted glucosamine (GlcNH 3 ؉ ) residues in heparan sulfate have important biological and pathophysiological roles. In this study, four GlcNH 3 ؉ -containing disaccharides were obtained from partially de-N-sulfated forms of heparin and the N-sulfated K5 polysaccharide by digestion with combined heparinases I, II, and III. These were identified as ⌬HexA-GlcNH 3 and ⌬HexA-(2S)-GlcNH 3؉ (6S). Digestions with individual enzymes revealed that heparinase I did not cleave at GlcNH 3 ؉ residues; howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…Here, we demonstrate an increased 10E4 antibody binding to the IPF HLF when compared with donor HLF, an effect that was reduced following treatment with heparinase I and III. The specificity of heparinase I directs its activity toward a linkage between N-and 6-Osulfated glucosamine and 2-O-sulfated iduronic acid, whereas heparinase III cleaves between non-sulfated or N-sulfated glucosamine and iduronic acid or glucoronic acid (18). Because immunoreactivity of IPF, but not donor, HLF was reduced after combined treatment with heparinase I and III, we concluded that IPF HLF contain more N-sulfated and 6-O-and 2-O-sulfated HS chains at the cell surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we demonstrate an increased 10E4 antibody binding to the IPF HLF when compared with donor HLF, an effect that was reduced following treatment with heparinase I and III. The specificity of heparinase I directs its activity toward a linkage between N-and 6-Osulfated glucosamine and 2-O-sulfated iduronic acid, whereas heparinase III cleaves between non-sulfated or N-sulfated glucosamine and iduronic acid or glucoronic acid (18). Because immunoreactivity of IPF, but not donor, HLF was reduced after combined treatment with heparinase I and III, we concluded that IPF HLF contain more N-sulfated and 6-O-and 2-O-sulfated HS chains at the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we investigated the role of differently sulfated HS structures in FXIIa binding by using heparinase I and heparinase III. N-and 6-O-sulfated glucosamine linked to 2-O-sulfated iduronic acid is a preferred dissacharide recognized by heparinase I, whereas heparinase III cleaves glycosidic linkage between N-acetylated or N-sulfated glucosamine and glucu- ronic acid (18). This distinct substrate specificity dictates degradation of high-or low-sulfated HS regions by heparinase I or heparinase III, respectively.…”
Section: Pgs Mediate Fxiia Binding To the Hlf Surface-becausementioning
confidence: 99%
“…To investigate this further, we repeated the above experiment but added porcine intestinederived heparan sulphate to the chlorate-containing culture medium instead of the bovine kidney-derived species. Heparan sulphate from porcine intestines possesses a lower degree of sulphation compared to that obtained from bovine kidney (33,34). We hypothesised that it may thus be less effective in blocking the effect of chlorate on cell adhesion.…”
Section: Expression Of Heparan Sulphate In Breast Cancer Tissuesmentioning
confidence: 99%
“…Also, Hep I does not cleave the domains of heparan sulfate that are in proximity to the protein backbone (the N-acetylated domains and transition zones), which are less sulfated. These regions, however, are cleaved by heparinase III (Hep III), which cleaves specifically between uronic acids (iduronic acid [IdoA] or glucuronic acid [GlcA]) and N-sulfated or N-acetylated glucosamine (GlcNSO 4 and GlcNAc, respectively) (17,70). These motifs are relatively common in heparan sulfate, and therefore, Hep III cleaves heparan sulfate more efficiently than Hep I (70).…”
Section: Lactoferrin Inhibits Fix-mediated Binding Of Hadv-31 Virionsmentioning
confidence: 99%
“…These regions, however, are cleaved by heparinase III (Hep III), which cleaves specifically between uronic acids (iduronic acid [IdoA] or glucuronic acid [GlcA]) and N-sulfated or N-acetylated glucosamine (GlcNSO 4 and GlcNAc, respectively) (17,70). These motifs are relatively common in heparan sulfate, and therefore, Hep III cleaves heparan sulfate more efficiently than Hep I (70). As expected, we found that Hep III treatment of FHs74Int cells efficiently prevented FX-mediated HAdV-5 binding, but FIX-mediated HAdV-31 binding was also efficiently reduced.…”
Section: Lactoferrin Inhibits Fix-mediated Binding Of Hadv-31 Virionsmentioning
confidence: 99%